POLA RETAK KOLOM YANG DIRETROFIT MENGGUNAKAN WIREMESH DAN SELF-COMPACTING CONCRETE AKIBAT BEBAN LATERAL - Syahrul Satar (Yayasan Nusantara Hasana Berdikari, 2026)
Retrofitting is one method used to restore the capacity, ductility, and stiffness of reinforced concrete columns that have been damaged by lateral loads such as earthquakes. This study analyzes the crack patterns in reinforced concrete columns that have been retrofitted using wire mesh and self-compacting concrete (SCC) based on experimental data from three specimens: control column (KK), fully retrofitted column (KR-1), and column retrofitted in the plastic hinge region (KR-2). Loading was performed cyclically with displacement control following SNI 7834:2012. The results showed that retrofitting with wire mesh and SCC significantly modified the crack pattern, delayed the appearance of initial cracks, reduced the number of cracks, and limited crack propagation in the plastic hinge area. KR-1 and KR-2 showed more concentrated flexural crack patterns that were not as extensive as those in KK, and had better final deformation and post-elastic capacity. In conclusion, the installation of wire mesh and SCC, either fully or only at the plastic hinge, was effective in controlling crack patterns and improving column performance against lateral loads.